Communication Strategies of the Multipurpose Syari'ah Cooperative of Musi Sejahtera Palembang in Improving the Welfare of the Members - Muhammad Taufik (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
The aim of this research was to identify the all-round business syari'ah cooperative development program,